2015
DOI: 10.1152/physrev.00025.2014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular and Intracellular Signaling for Neuronal Polarity

Abstract: Neurons are one of the highly polarized cells in the body. One of the fundamental issues in neuroscience is how neurons establish their polarity; therefore, this issue fascinates many scientists. Cultured neurons are useful tools for analyzing the mechanisms of neuronal polarization, and indeed, most of the molecules important in their polarization were identified using culture systems. However, we now know that the process of neuronal polarization in vivo differs in some respects from that in cultured neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 382 publications
(577 reference statements)
0
121
1
Order By: Relevance
“…Pyramidal neurons first extend multiple minor processes and are called multipolar (MP) cells in intermediate zone (IZ). These MP cells subsequently transform into bipolar (BP) cells with a trailing process and a leading process, which finally develop into an axon and a dendrite, respectively 2, 3 . BP cells are completely polarized and migrate toward the cortical plate (CP).…”
Section: Resultsmentioning
confidence: 99%
“…Pyramidal neurons first extend multiple minor processes and are called multipolar (MP) cells in intermediate zone (IZ). These MP cells subsequently transform into bipolar (BP) cells with a trailing process and a leading process, which finally develop into an axon and a dendrite, respectively 2, 3 . BP cells are completely polarized and migrate toward the cortical plate (CP).…”
Section: Resultsmentioning
confidence: 99%
“…Rho-kinase phosphorylates MYPT1 and inactivates myosin light chain phosphatase, thereby increasing the phosphorylation of MLC followed by smooth muscle contraction (Amano et al, 2010a). For the last 10 years, many substrates of Rho-kinase were studied in neurons, and it was observed that the phosphorylated proteins control nerve axon extension (Namba et al, 2015). In contrast to vascular cells and neuronal cells, less is known about the substrates of Rho-kinase in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Nascent projection neurons are embedded in a heterogeneous environment and cell-cell interactions are likely to play an important role in neuronal polarization (Jossin, 2011; Gartner et al, 2015; Namba et al, 2015). It has been suggested that the radial glial scaffold, on which neurons perform locomotion in the IZ, could be involved in the MP-to-BP transition.…”
Section: Extracellular Cues Controlling Projection Neuron Polarity Inmentioning
confidence: 99%
“…In such context, it has been proposed that the interaction of multipolar cells and RGPs mediated by N-cadherin leads to the establishment of axon-dendrite polarity through polarized distribution of active RhoA in the neurite contacting the RGC and active Rac1 on the opposite side where the axon is formed (Xu et al, 2015). Physical interactions between pioneering axons from earlier generated neurons and the dynamic neurites from newly born neurons have been shown to contribute to polarization in MP neurons (Namba et al, 2014, 2015). These interactions involve the cell adhesion molecule transient axonal glycoprotein 1 (TAG-1).…”
Section: Extracellular Cues Controlling Projection Neuron Polarity Inmentioning
confidence: 99%